Factors Related to Health Protocol Implementation Among Covid-19’s Survivor in Surabaya - Widayanti, Linda Prasetyaning; Andiarna, Funsu (International Conference on Sustainable Health Promotion, 2021)
It is almost two years for Covid-19 pandemic occurred in Indonesia. There were over 198 million cases and 4 million deaths since March 2020. Vaccination and implementation of health protocol is way out to quit Covid-19 pandemic. There were hundreds of million Covid-19 survivors had second infection after the first attack. This means that even someone has been infected by Covid-19 for the first time, if he didn’t do health protocol properly, it is possible to get second infection. Covid-19 could be mutated rapidly. Someone who has been exposed by one variant of Covid-19 could be easily infected by other variant in the future. Covid-19’s survivors are equal with other healthy people. They have to do health protocol to prevent transmission of the virus. This research aimed to analyze factors related to health protocol implementation among Covid-19’s survivors in Surabaya. This research’s methode was analytic observational with crosssectional approach. 100 Covid’s survivors in Surabaya were choosen by Simple Random Sampling. Data collected by Google Form and analized by Cramer’s V. The result of this research concluded that 73% respondents were women, 77% aged 18-25 years old, 61% were students and 61% had good knowledge. The implementation of health protocol were 71% among respondents. Gender (p=0.010), age (p=0.017) and knowledge (p=0.004) were related to health protocol implementation while occupation (p=0.076) variable wasn’t. Self awareness is needed to do health protocol during pandemic. Health protocol aimed to reduce transmission of Covid-19